截割减速器参数化设计数据库管理系统的研究 - 李晓豁; 顾红兵 (Jixie chuandong)
A database management system of longitudinal roadheader cutting gearbox parametric design has been developed by ADO database access technology,using Visual C++ 6.0 as development tool and SQL Server 2000 as background database.Therefore,data share and consistency is realized in parametric design,and,query and edition of basic information and dimension parameters of gearbox parts is also became conveniently for users.Moreover,the function and implementation method of this database management system is also described in detail.So it can be used as a reference for the database management system development of other mechanical products.